Combined anthelmintic treatments to control resistant nematodes in cattle: pharmacokinetic and field efficacy evaluations - Cantón, Candela (2022)
In an attempt to minimize therapeutic failures following anthelmintic treatments, the combined use of nematodicidal compounds with different mechanisms of action has been proposed. A pharmaco-parasitological assessment of different nematodicidal combinations was performed on two commercial cattle farms in Argentina(A and B). Two different nematodicidal combinations of a macrocyclic lactone(ML) and a benzimidazole(BZD) anthelmintics were evaluated in a multi-resistant field scenario. Ivermectin(IVM)+ricobendazole(RBZ) both given subcutaneously and abamectin(ABA)+oxfendazole(OXF) both given orally were assessed in calves naturally infected with gastrointestinal nematodes resistant to both chemical families. The observed pharmacokinetic(PK) data demonstrated that the co-administration of two anthelmintics did not modify the plasma PK disposition of either drug in cattle. In fact, no adverse PK interactions were observed after each combined treatment, with no differences in PK parameters(P>0.05) observed between the single-drug and the combined-based strategies. While the observed initial efficacies were 40%(IVM), 64%(RBZ) and 90%(IVM+RBZ)(Farm A), the egg reductions were 54%(IVM), 84%(RBZ) and 98%(IVM-RBZ)(Farm B). After repeated annual(over 5 years) use of the same combination on both farms, the efficacy of the combined treatment decreased to 83% on Farm A. In contrast, the efficacy of the combination IVM-RBZ remained at 93% efficacy in Farm B .To optimize drug activity against those highly bi-resistant nematode population, oral combined treatments were assayed. Efficacies of ABA alone, OXF alone and the co-administration ABA+OXF were 62%, 88% and 99%, respectively(Farm A) and, 92%, 95% and 98%, respectively(Farm B).The Haemonchus spp. were resistant to ABA, the Ostertagia spp. were resistant to OXF and both anthelmintics failed to control the Cooperia spp.However, the combination ABA+OXF was the only treatment that achieved 99-100% efficacy against all genera, indicating the presence of an additive effect. Overall, anthelmintic combinations can be useful to optimize the control of resistant gastrointestinal nematodes of cattle.However, its rational use should be strongly supported by pre-treatment diagnosis and considering the epidemiological situation of each individual farm.